Prevalence of oral manifestations of hypophosphatemic rickets in patients treated in a Peruvian Pediatric Hospital. - Janet Ofelia Guevara-Canales; Nathali Cardenas-Zuñiga; Miguel Chavez-Pastor; Milana Trubnykova; Rafael Morales-Vadillo (Universidad de Concepción., 2020)
Objective: To describe the prevalence of oral manifestations of hypophosphatemic rickets in patients treated in a Peruvian referral pediatric hospital during the years 2012-2016. Material and methods: An observational, descriptive, retrospective, cross-sectional study was carried out. The sample consisted of patients diagnosed with hypophosphatemic rickets who attended the outpatient clinic of the Stomatology Service and the Genetics Service of the National Institute of Child Health (INSN), Lima, Peru, between the years 2012-2016. The research project was assessed and approved by the Research Ethics Committee of the Health Service. Medical records stored in a database of the health institution with the Code CIE E83.3, which corresponds to the diagnosis of Hypophosphatemic Rickets, were requested for the study. Results: Fifteen children received health care, of which only 10 were treated at the Stomatology Service. The distribution of the data was obtained from these 10 patients according to the proposed objective. A higher frequency of gingival lesions was found at the soft tissue level (41.18%); at the bone tissue level, only one case of dentigerous cyst was observed; and at the dental level, 90% of the patients had dental caries. Conclusion: The most frequent oral manifestations of hypophosphatemic rickets in pediatric patients treated at the National Institute of Child Health (2012-2016) were gingivitis and dental caries.